Databases and information systems : 12th International Baltic Conference, DB & IS 2016, Riga, Latvia, July 4-6, 2016, Proceedings /: 12th International Baltic Conference, DB & IS 2016, Riga, Latvia, July 4-6, 2016, Proceedings. (2016) - Unknown
No abstract available